Development of Environmentally Friendly Math Learning Media "Situng" First-Grade Elementary School - Fatmawati, Rizka Silvia; Habiby, Wahdan Najib (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
Math is one of the materials that students are afraid of. The lack of student interest in mathematics is due to the absence of interesting learning media, especially in arithmetic operations. The objectives of this study are: 1) to increase students' interest in mathematics subjects, especially counting operations, 2) to test the effectiveness of environmentally friendly media "situng" in the learning process of grade 1 mathematics. This research is a Research and Development (R&D) development research that uses the 4D model with the Define, Design, Develop, Disseminate process. This research data collection technique uses observation, interviews, questionnaires, pre-test and post-test questions. While the data collection instrument of this study used student questionnaires. The assessment instrument based on the validity test of media experts and teachers based on the Aiken's V validity test with the results of 0.916 with a very high description, the validity test score with the results of r count higher than r table is declared (Valid), the reliability test with the final result of 0.924 with a critical limit of 0.6 is declared (Reliable), the Normality test with a significance result of 0.797 with a significance limit of more than 0.05 is said (Normal) and the T test with a significance of 0.047 has a value less than 0.05 said to be influential. Thus, the environmentally friendly math learning media "situng" is declared valid, and effective for increasing the interest in learning mathematics of first-grade elementary school students.